2020
DOI: 10.3390/sym12081267
|View full text |Cite
|
Sign up to set email alerts
|

Inflation with Scalar-Tensor Theory of Gravity

Abstract: The latest released data from Planck in 2018 put up tighter constraints on inflationary parameters. In the present article, the in-built symmetry of the non-minimally coupled scalar-tensor theory of gravity is used to fix the coupling parameter, the functional Brans–Dicke parameter, and the potential of the theory. It is found that all the three different power-law potentials and one exponential pass these constraints comfortably, and also gracefully exit from inflation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Of course, slow-roll inflation with quartic potential may be studied, but in more involved theories of gravity, e.g. in non-minimally coupled scalar-tensor theories [109][110][111] or in higher-order theories [112][113][114], in which an effective potential with a flat section comes into play. It is important to mention that F(T ) theories have also given rise to some disputes about an intriguing and essential feature: the action of the theory is not invariant under…”
Section: Discussionmentioning
confidence: 99%
“…Of course, slow-roll inflation with quartic potential may be studied, but in more involved theories of gravity, e.g. in non-minimally coupled scalar-tensor theories [109][110][111] or in higher-order theories [112][113][114], in which an effective potential with a flat section comes into play. It is important to mention that F(T ) theories have also given rise to some disputes about an intriguing and essential feature: the action of the theory is not invariant under…”
Section: Discussionmentioning
confidence: 99%
“…Of-course, slow roll inflation with quartic potential may be studied, but in more involved theories of gravity, e.g. in non-minimally coupled scalar-tensor theories [109][110][111] or in higher order theories [112][113][114], in which an effective potential with a flat section comes into play. It is important to mention that F (T ) theories have also given rise to some disputes about an intriguing and essential feature: for example, the action of the theory is not invariant under local Lorentz transformations of the tetrad [40,52,74,75], and also it suffers from the unresolved pathology of 'Branched Hamiltonian' that we shall discuss in future.…”
Section: Discussionmentioning
confidence: 99%

Inflation with F(T) Teleparallel Gravity

Chakrabortty,
Sk,
Sanyal
et al. 2021
Preprint
Self Cite
“…We have seen that both the forms F(T) of generalized metric teleparallel gravity theory presented in (44) and (48) admit FLRW type radiation and early matter dominated eras, and can trigger accelerated expansion in the late stage of cosmological evolution. Further, both the forms are validated by energy conditions.…”
Section: Slow Roll Inflationmentioning
confidence: 97%
“…Study of the other three connections have been initiated recently [46,47]. More recently, it has been shown that all these three connections can also explain the cosmic evolutionary history, for a linear form of F(Q) = f 0 Q, without further modification [48].…”
Section: Symmetric Teleparallel F(q) Theory Of Gravitymentioning
confidence: 99%